Propuesta para la gestión de residuos sólidos y seguimiento del mismo en el Colegio Quintín Lame del resguardo de Tacueyó, municipio de Toribío, departamento del Cauca. (2024)
This work consisted of solving the problem faced by the Quintín Lame school, which is located in the Tacueyó reservation, municipality of Toribio, department of Cauca, by carrying out a solid waste management plan (MSW) in the school through MSW utilization campaigns to minimize the impacts they generate in landfills or landfills to address this problem. The methodology used consisted of characterizing the waste generated at the school, training on the correct management of MSW and monitoring of ecological points. previously established and the digester bales implemented.